The Information Technology and Business Process Outsourcing Industry: Diversity and Challenges in Asia - Raja Mikael Mitra (Asian Development Bank (ADB), 2013)
Some countries and regions have been more successful than others in developing information technology-business process outsourcing (IT-BPO) services industries. India and the Philippines in particular have offered educated human resources at low cost, attractive fiscal incentives, and industrial parks although these factors alone do not explain the rapid growth of the industry there as other countries also had these strengths but failed to develop industries as rapidly. A wide range of factors driving and constraining industry development must be taken into account, namely human resources; financial, infrastructure, technology, legal, and regulatory developments; the roles of foreign companies, diasporas, and of indigenous entrepreneurs; the government; industry associations; civil society; production, trade, and knowledge networks; and the interplay of all these factors locally, nationally, and internationally. This analysis of IT-BPO industry developments in Asia points to continued expansion in domestic, regional, and global demand and supply. There is a need for timely, concerted efforts by key stakeholders to define strategies, programs, and projects to respond to opportunities and challenges at all levels. Experiences from Asian economies can offer lessons, but each situation has its own peculiarities. There is no single approach to developing an IT-BPO industry.
hdl:11540/2295
Keywords: O14; 330; information technology; business process outsourcing; software industry; offshoring; services; knowledge economy; India; ASEAN; Asia